Steifigkeit axial beanspruchter Vollgewindeschrauben - Blaß, Hans JoachimSteige, Yvonne (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Holzbau und Baukonstruktionen, 2018)
The load-bearing capacity of axially loaded fully threaded screws can be determined correctly according to the acknowledged rules of technology. Whereas the currently available calculation models for the axial stiffness are clearly different from one another. In this research, different test methods for the determination of the axial stiffness were tested and analysed. Based on the test results, a test method was finally identified and calculation models were developed.